VPO catalyst and application thereof in preparation of maleic anhydride through n-butane oxidation
By preparing VPO spherical catalysts with linear channels, the problems of short life and many by-products of existing VPO catalysts are solved, more efficient catalytic performance and mechanical strength are achieved, and the service life of the catalyst is extended.
Patent Information
- Application Number
- CN202310770782.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-06-28
AI Technical Summary
During the use of existing VPO catalysts, there are problems such as many by-products, serious coking phenomenon, and short catalyst life, resulting in phosphorus loss and catalytic performance degradation.
By preparing VPO spherical catalysts with linear channels, using the special combination of mineralizers and template agents, a long chain structure is formed and linear channels are left after high-temperature calcination, which enhances the mechanical strength and wear resistance of the catalyst, reduces phosphorus loss, and prolongs the Catalyst life.
The catalyst is achieved longer life, maintains efficient conversion capacity, reduces by-product generation, and improves the service life and mechanical strength of the catalyst.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0004307775350000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysis, and in particular to a VPO catalyst and application thereof in preparing maleic anhydride by oxidation of n-butane. Background Art
[0002] Maleic anhydride is abbreviated as maleic anhydride, also known as maleic anhydride. It is one of the three major organic anhydrides in the chemical industry, second only to phthalic anhydride and acetic anhydride. It is a very important organic chemical raw material and has a wide range of application markets in the petroleum industry, pharmaceutical intermediates, food processing and construction industries. In recent years, with the development of natural gas in my country, natural gas transportation facilities have become more convenient, and natural gas has begun to become the mainstream fuel gas. The return of workers has caused n-butane to lose its main market, and the price of n-butane has dropped significantly. N-butane has the advantages of low price, relatively light pollution, and better atomic economy, which makes butane oxidation to maleic anhydride have better economic benefits. Compared with the past benzene method to produce maleic anhydride, the start-up volume of the butane oxidation method to prepare maleic anhydride has gradually increased, becoming the mainstream of the chemical industry.
[0003] Among the catalysts for the oxidation of n-butane to maleic anhydride, vanadium phosphorus oxide (VPO) catalysts have been proven to be the most effective catalysts for the oxidation of n-butane to maleic anhydride. Among the numerous preparation methods, the preparation of VPO catalysts by organic solvents is a simple method for preparing VPO catalysts for maleic anhydride. The organic solvent method is to carry out a synthesis reaction of vanadium oxide compounds, phosphorus compounds and promoters in selected organic solvents such as esters, alcohols, aldehydes, etc. After a period of reaction, a catalyst precursor containing VPO is generated, which is then separated from the solid and liquid, washed, dried, calcined, and then pressed into particles with a specific appearance to obtain the desired VPO catalyst. The catalyst can be activated by gas before the butane oxidation reaction to achieve the best catalytic effect.
[0004] Although VPO catalysts have been industrialized for many years and have been continuously improved, commercial VPO catalysts still have a lot of by-products, resulting in serious coking, catalyst damage and failure, etc., which shortens the catalyst life. Therefore, research work to extend the operating life of VPO catalysts has been ongoing. Summary of the invention
[0005] In view of the problems existing in the prior art, it is necessary to reduce catalyst wear, reduce by-products, solve the problem of phosphorus loss during the use of VPO catalysts leading to decreased catalytic performance and increased by-products, and thus extend the service life of the catalyst during use. One of the purposes of the present invention is to provide a VPO catalyst that can obtain a longer catalytic life when used for the oxidation of n-butane to maleic anhydride. First, a VPO spherical catalyst with linear pores is prepared, such as the attached Figure 1As shown. During the preparation process, through the special combination of mineralizer and template, template B will form balls around the hydrophobic end due to the presence of hydrophilic and hydrophobic ends in its structure, and under a certain temperature and humidity and weak alkaline environment, the multiple hydrogen bonds of the mineralizer make these template microspheres form long chains, and the silanization ability of the silicon source reagent enables it to coat these long chains into balls. The subsequent long-chain organic molecules leave linear channels after high-temperature calcination, and the remaining part forms a spherical catalyst containing VPO active sites.
[0006] These linear channels can ensure that there is still sufficient specific surface area and accessible active sites after the subsequent loading of the VPO catalyst, thereby ensuring the catalytic activity of the catalyst and reducing the formation of by-products. At the same time, under the protection of silicon, the mechanical strength and wear resistance of the VPO catalyst can be greatly enhanced, and the phosphorus loss rate of the VPO catalyst can be reduced, thereby allowing the VPO catalyst to exhibit a longer service life.
[0007] The process method provided by the present invention has the advantages of simple catalyst preparation, stable performance, high strength and long service life, simple preparation method and low cost, which is conducive to large-scale industrial application.
[0008] In order to achieve the above-mentioned invention object, the specific technical scheme is as follows:
[0009] A method for preparing a spherical VPO catalyst having linear pores, the method comprising the following steps:
[0010] S1: dissolving the mineralizer A and the template B in water, stirring and mixing, adding alcohol and oxidized vanadium, heating and refluxing, adding phosphoric acid to continue the reaction, then adding a silicon source, washing and drying the obtained solid, and calcining to remove the template to obtain a precursor;
[0011] S2: Add small molecule alcohol and water to the precursor, and obtain catalyst particles by pressing, demolding, drying, crushing and screening.
[0012] In one embodiment of the present invention, the mineralizer A described in S1 is a compound having multiple hydrogen bonds on both sides of the molecular structure along the axis, preferably one or more of 2-amino-2-hydroxymethyl-1,3-propanediol, 3-aminophenol, 4-amino-5-methylpyridine-2-ol, 6-amino-2-hydroxymethyl-n-1-hexanol, 6-amino-2-hydroxymethyl-n-hexane-1-ol, tromethamine, 4-dimethylamino-1-butanol, 2-hydroxymethylaminoethanol, and (S)-2-Boc-amino-1,4-butanol.
[0013] In one embodiment of the present invention, the template B described in S1 is an organic ammonium salt, preferably one or more of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium p-toluenesulfonate, and octadecyltrimethylammonium chloride; preferably, the molar ratio of mineralizer A:template B=1:(0.1-120); preferably, the molar ratio of template B:silicon source:water=1:(1-100):(100-10000).
[0014] In one embodiment of the present invention, the alcohol described in S1 is a C1-C12 small molecule alcohol, preferably one or more of methanol, benzyl alcohol, ethanol, isobutanol, and n-hexanol.
[0015] In one embodiment of the present invention, the vanadium in the oxidation state described in S1 is a vanadium oxide compound, preferably one or more of vanadium dioxide, vanadium trioxide, and vanadium pentoxide; preferably, the molar ratio of phosphorus element to vanadium element = 1:(0.1-100).
[0016] In one embodiment of the present invention, the silicon source described in S1 is a silicon compound, preferably one or more of neutral silica sol, fumed silica, white carbon black, tetraethyl orthosilicate, silicic acid, trimethylsilyl acetate, and tetraacetic silicon; preferably, the molar ratio of vanadium element: alcohol: silicon element in S1 = 1: (0.1-100): (0.1-100).
[0017] In one embodiment of the present invention, the stirring and mixing in S1 is carried out under constant temperature and humidity conditions; preferably, the temperature is 10° C.-80° C., the humidity is 5%-80%, and the time is 0.5-12 h.
[0018] In one embodiment of the present invention, the heating reflux temperature in S1 is 50-100° C., and the reflux time is 1-24 h.
[0019] In one embodiment of the present invention, the calcination temperature in S1 is 400-900°C and the calcination time is 2-10h.
[0020] In one embodiment of the present invention, the VPO catalyst obtained in S1 is microscopically spherical with linear channels.
[0021] In one embodiment of the present invention, C1-C12 small molecule alcohol is added to S2, preferably one or more of methanol, ethanol, n-propanol, n-butanol, ethylene glycol, 1,4-butanediol, n-hexanol, and lauryl alcohol; preferably, the mass ratio of alcohol to water is 1:(0.1-100); preferably, the total mass of alcohol and water accounts for 1%-100% of the mass of the precursor.
[0022] In one embodiment of the present invention, the particle size screened in S2 is 20-60 mesh.
[0023] Another object of the present invention is to provide a spherical VPO catalyst having linear pores.
[0024] A spherical VPO catalyst with linear pores is prepared by the above method. The catalyst is microscopically spherical with linear pores.
[0025] Another object of the present invention is to provide a process for prolonging the life of the VPO catalyst used in the oxidation of n-butane to prepare maleic anhydride.
[0026] A process for extending the life of a VPO catalyst used for preparing maleic anhydride by oxidation of n-butane. The process adopts a catalyst prepared by the above method, or adopts the above catalyst. The catalyst adopted by the process is microscopically spherical with linear pores.
[0027] In a specific embodiment of the present invention, butane oxidation is carried out in a fixed bed reactor to produce maleic anhydride: the molded VPO catalyst is loaded into a tubular reactor, a butane mixed gas is introduced into the tubular reactor for catalyst activation, the gas is heated for preheating, and then the preheated mixed gas is introduced into the tubular reactor. After activation, the reaction temperature is increased, and sampling of the reaction is started. The tail gas is connected to an online TCD detector to analyze the results at different time points, thereby producing a maleic anhydride product.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The VPO catalyst prepared by the present invention has linear pores. Compared with the conventional supported VPO catalyst, the active centers of the VPO catalyst prepared by the present invention can be evenly dispersed in the linear pores, and the distribution is uniform, and the transfer conversion rate is very good, thereby ensuring the catalytic performance of the catalyst.
[0030] (2) The VPO catalyst prepared by the present invention is protected by silicon, which greatly reduces wear and phosphorus loss during use, can maintain high conversion efficiency during long-term operation, and greatly extends the service life of the catalyst.
[0031] (3) The process pipeline modification scheme designed by the present invention is simple, requires little space, and is applicable to industrial implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the preparation of VPO spherical catalyst with linear pores;
[0033] Figure 2is a SEM picture of the VPO catalyst with linear pores prepared by the present invention;
[0034] Figure 3 This is a TEM image of the VPO catalyst with linear pores prepared in the present invention. DETAILED DESCRIPTION
[0035] The following are some embodiments to further illustrate the content of the present invention, but the present invention is not limited to these embodiments.
[0036] Raw material information: 2-amino-2-hydroxymethyl-1,3-propanediol, ARK, 98%; hexadecyltrimethylammonium p-toluenesulfonate, 98%; vanadium pentoxide, 99.5%; benzyl alcohol, 99%; isobutyl alcohol, 99.5% chromatographically pure; tetraethyl orthosilicate, 99%; ethanol, 99.7% AR; phosphoric acid, 85% aqueous solution; 3-aminophenol, 99%; hexadecyltrimethylammonium bromide, 99%; hexadecyltrimethylammonium chloride, 99%; vanadium dioxide, 99%; tromethamine, 99.8%; methanol, 99.5%, n-hexanol, 99%, tetrapropylammonium hydroxide, 25% aqueous solution; tetraethylammonium hydroxide, 25% aqueous solution; silicic acid, 99.9%; 4-dimethyl-1-butanol, 99%; 2-hydroxy-aminoethanol, 99%. Beijing Innochem Technology, Innochem.
[0037] Analysis and characterization: Scanning electron microscope (SEM), model JEOL JSM-7800F; Transmission electron microscope (TEM), model JEOL JEM-2100.
[0038] Example 1
[0039] First, 0.01g of 2-amino-2-hydroxymethyl-1,3-propanediol and 4g of hexadecyltrimethylammonium p-toluenesulfonate were dissolved in 500mL of deionized water, and stirred for 0.5h at a humidity of 20% and a temperature of 50°C. 18.1g of V2O5, 5.4g of benzyl alcohol, 7.4g of isobutyl alcohol and 40g of tetraethyl orthosilicate reagent were taken, heated to 80°C and refluxed for 24h, and then 19.6g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the various residual templates. Then, it was dried in an oven at 80°C for 12h, and the dried sample was ground and pulverized to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 500°C for 5 hours to remove the hard template to obtain a spherical VPO catalyst with linear channels; 5g of catalyst precursor, 0.5g of deionized water and 0.5g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 100°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear channels.
[0040] Example 2
[0041] First, 0.01g 3-aminophenol and 2.9g hexadecyltrimethylammonium chloride were dissolved in 500mL deionized water, and stirred for 0.5h at 10% humidity and 70°C. 8.3g VO2, 5.4g benzyl alcohol, 7.4g isobutyl alcohol and 180g tetraethyl orthosilicate reagent were taken, heated to 100°C and refluxed for 5h, and then 0.12g phosphoric acid was added to continue the reaction for 2h, and the generated solid was filtered and washed with deionized water to fully wash the residual templates. Then, the sample was dried in an oven at 105°C for 12h, and the dried sample was ground to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 550°C for 6 hours to remove the hard template to obtain a spherical VPO catalyst with linear pores; 5g of catalyst precursor, 0.5g of deionized water and 4.5g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 105°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear pores.
[0042] Example 3
[0043] First, 4.84g of tromethamine and 1.46g of hexadecyltrimethylammonium bromide were dissolved in 700mL of deionized water, and stirred for 1h at 80% humidity and 70°C. 1g of V2O5, 1.6g of methanol, 18g of n-hexanol and 20g of fumed silica were taken, heated to 80°C and refluxed for 5h, and then 5g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the various residual templates. Then, the sample was dried in an oven at 105°C for 12h, and the dried sample was ground to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 900°C for 2 hours to remove the hard template to obtain a spherical VPO catalyst with linear pores; 5g of catalyst precursor, 0.4g of deionized water and 4g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 105°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear pores.
[0044] Example 4
[0045] First, 0.01g of 2-amino-2-hydroxymethyl-1,3-propanediol and 0.8g of tetrapropylammonium hydroxide aqueous solution were dissolved in 100mL of deionized water, and stirred for 2.5h at 30% humidity and 65°C. 0.83g of VO2, 2.24g of methanol, 2.22g of isobutyl alcohol and 7.6g of silicic acid reagent were taken, heated to 70°C and refluxed for 6h, and then 0.01g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the residual templates. Then, it was dried in an oven at 80°C for 12h, and the dried sample was ground and crushed to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 650°C for 5 hours to remove the hard template to obtain a spherical VPO catalyst with linear channels; 5g of catalyst precursor, 4g of deionized water and 0.04g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 100°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear channels.
[0046] Example 5
[0047] First, 0.01g of 2-amino-2-hydroxymethyl-1,3-propanediol and 4g of hexadecyltrimethylammonium p-toluenesulfonate were dissolved in 300mL of deionized water, and stirred for 0.4h at 90% humidity and 100°C. 18.1g of V2O5, 5.4g of benzyl alcohol, 7.4g of isobutyl alcohol and 40g of tetraethyl orthosilicate reagent were taken, heated to 75°C and refluxed for 2h, and then 19.6g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the various residual templates. Then, it was dried in an oven at 80°C for 12h, and the dried sample was ground and pulverized to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 500°C for 2.5 hours to remove the hard template to obtain a spherical VPO catalyst with linear channels; 5g of catalyst precursor, 0.02g of deionized water and 0.03g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 100°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear channels.
[0048] Example 6
[0049] First, 0.01g of 4-dimethylamino-1-butanol and 4.8g of tetraethylammonium hydroxide aqueous solution were dissolved in 20mL of deionized water, and stirred for 6.5h at 60% humidity and 40°C. 0.7g of VO2, 43g of benzyl alcohol, 29.6g of isobutyl alcohol and 40.8g of fumed silica were taken, heated to 75°C and refluxed for 8h, and then 0.82g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the residual templates. Then, the sample was dried in an oven at 80°C for 12h, and the dried sample was ground to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 800°C for 7 hours to remove the hard template to obtain a spherical VPO catalyst with linear pores; 5g of catalyst precursor, 2.3g of deionized water and 2.2g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 100°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear pores.
[0050] Example 7
[0051] First, 0.91g of 2-hydroxymethylaminoethanol and 1.36g of hexadecyltrimethylammonium toluenesulfonate were dissolved in 450mL of deionized water, and stirred for 12h at 30% humidity and 60°C. 0.16g of VO2, 0.2g of benzyl alcohol and 12.6g of fumed silica were taken, heated to 62°C and refluxed for 6h, and then 0.1g of phosphoric acid was added to continue the reaction for 2h. The generated solid was filtered and washed with deionized water to fully wash the residual templates. Then, the sample was dried in an oven at 80°C for 12h, and the dried sample was ground to obtain a powder with a template. The obtained powder was then placed in a muffle furnace and calcined at 400°C for 10 hours to remove the hard template to obtain a spherical VPO catalyst with linear pores; 5g of catalyst precursor, 1g of deionized water and 1g of anhydrous ethanol were taken, stirred and mixed evenly, and the mixture was filled into a cylindrical mold, pressed at 0.3 MPa for 10 minutes to form, and after demolding, it was placed in an oven and dried at 100°C for 24 hours, and crushed and sieved into 20-60 mesh VPO catalysts with linear pores.
[0052] Comparative Example 1
[0053] The conventional VPO catalyst preparation method was used to prepare the conventional VPO catalyst for the comparative example.
[0054] Take 18.1g V2O5 and 5.4g benzyl alcohol, 7.4g isobutanol, heat to 100℃ and reflux for 3h, then add 19.6g phosphoric acid and continue to react for 3h, and filter and wash the generated solid with deionized water. Then dry it in an oven at 100℃ for 12h, and grind the dried sample. Then put the obtained powder in a muffle furnace and roast it at 500℃ for 6h to obtain VPO catalyst; take 5g catalyst precursor and 6g deionized water and 4ml anhydrous ethanol, stir and mix evenly, fill the mixture into a cylindrical mold, press at 0.3mpa for 10min to form, put it in an oven at 100℃ to dry for 24h after demolding, and crush and screen it into 20-60 mesh VPO catalyst.
[0055] The butane oxidation to maleic anhydride was carried out in a fixed bed reactor. The VPO catalyst after molding was loaded into the tubular reactor with a loading height of 3 cm and an aspect ratio of 2. A customized butane mixed gas with a concentration of 1% was introduced into the tubular reactor for catalyst activation. The gas was heated to 200°C at a rate of 25°C / h for preheating, and then the preheated gas was heated at a pressure of 0.15 MPa for 1000 h. -1 The mixed gas is introduced into the tubular reactor at an air velocity of , and after 24 hours of activation, the reaction temperature is increased to 410°C, and sampling of the reaction is started. The tail gas is connected to an online TCD detector to analyze the results at different time points. The experimental results are as follows, which show that the life of the catalyst of the present application is greatly extended.
[0056]
[0057]
Claims
1. A method for preparing a spherical VPO catalyst having linear pores, characterized in that: The method comprises the following steps: S1: dissolving the mineralizer A and the template B in water, stirring and mixing, adding alcohol and oxidized vanadium, heating and refluxing, adding phosphoric acid to continue the reaction, then adding a silicon source, washing and drying the obtained solid, and calcining to remove the template to obtain a precursor; S2: Add small molecule alcohol and water to the precursor, and obtain catalyst particles by pressing, demolding, drying, crushing and screening.
2. The method according to claim 1, characterized in that S1 The mineralizer A is a compound having multiple hydrogen bonds on both sides of the axis of the molecular structure, preferably one or more of 2-amino-2-hydroxymethyl-1,3-propanediol, 3-aminophenol, 4-amino-5-methylpyridine-2-ol, 6-amino-2-hydroxymethyl-n-1-hexanol, 6-amino-2-hydroxymethyl-n-hexane-1-ol, tromethamine, 4-dimethylamino-1-butanol, 2-hydroxymethylaminoethanol, (S)-2-Boc-amino-1,4-butanol; And / or, the template B in S1 is an organic ammonium salt, preferably one or more of tetraethylammonium bromide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium p-toluenesulfonate, and octadecyltrimethylammonium chloride; Preferably, the molar ratio of mineralizer A:template B=1:(0.1-120); Preferably, the molar ratio of template B: silicon source: water = 1: (1-100): (100-10000); And / or, the alcohol in S1 is a C1-C12 small molecule alcohol, preferably one or more of methanol, benzyl alcohol, ethanol, isobutanol, and n-hexanol; And / or, the vanadium in the oxidation state described in S1 is a vanadium oxide compound, preferably one or more of vanadium dioxide, vanadium trioxide, and vanadium pentoxide; Preferably, the molar ratio of phosphorus to vanadium = 1:(0.1-100); And / or, the silicon source in S1 is a silicon compound, preferably one or more of neutral silica sol, fumed silica, white carbon black, ethyl orthosilicate, silicic acid, trimethylsilyl acetate, and silicon tetraacetate; Preferably, the molar ratio of vanadium element: alcohol: silicon element in S1 is 1: (0.1-100): (0.1-100).
3. The method according to claim 1 or 2, characterized in that: The heating reflux temperature in S1 is 50-100° C., and the reflux time is 1-24 h; And / or, the calcination temperature in S1 is 400-900° C. and the calcination time is 2-10 h.
4. The method according to any one of claims 1 to 3, characterized in that The VPO catalyst obtained by S1 is microscopically spherical with linear pores.
5. The method according to claim 1, characterized in that Add C1-C12 small molecule alcohol to S2, preferably one or more of methanol, ethanol, n-propanol, n-butanol, ethylene glycol, 1,4-butanediol, n-hexanol, and lauryl alcohol; Preferably, the mass ratio of alcohol to water is 1:(0.1-100); Preferably, the total mass of alcohol and water accounts for 1%-100% of the mass of the precursor; And / or, the particle size screened in S2 is 20-60 mesh.
6. A spherical VPO catalyst with linear pores, prepared by the method according to any one of claims 1 to 5, characterized in that: The catalyst is microscopically spherical with linear pores.
7. A process for extending the life of a VPO catalyst for producing maleic anhydride by oxidation of n-butane, the process comprising using a catalyst prepared by the method of any one of claims 1 to 5, or using a catalyst according to claim 6, characterized in that: The catalyst used in the process method is microscopically spherical with linear pores.
Citation Information
Patent Citations
Method of regenerating maleic anhydride produced from n-butane fluidized-bed catalyst
CN101036891A
Loading type catalyst for preparing maleic anhydride through n-butane oxidation and preparation method of catalyst
CN106140125A
Hydroxyalkyl substituted pyrido-7-pyrimidin-7-ones
SG122316A1